Kinetic Study Of Biosorption And Bioreduction Of Hexavalent Chromium By Unmodified Sawdust - Ng, Zhung Gia (2013)
The effects of initial Cr(VI) concentration, initial pH and sawdust dosage on Cr(VI) biosorption-bioreduction were evaluated at the initial Cr(VI) concentration range of 250 -1500 μM, pH range of 2.0 - 4.0 and dosage range of 2 – 4 g L-1, respectively. The effects of phenol and Zn(II) were evaluated at the Cr(VI):phenol and Cr(VI):Zn(II) molar ratios of 1:0, 2:1, 1:1, 1:3 and 1:5. A control experiment was conducted under the conditions: initial Cr(VI) concentration of 500 μM, initial pH of 2.0, sawdust dosage of 4 g L-1, shaking speed of 250 rpm and temperature of 25 (±1) oC to show that Cr(VI) removal by sawdust involved biosorption and bioreduction.